The Application of Alizarin Red S in the Fluid-inclusion Homogenization Temperature Measurement of Carbonate Rocks from the Middle Permian Qixia Formation, Western Sichuan Basin - LAN Ye-fang; HUANG Si-jing; YUAN Tao; HU Bo; HUANG Shu-guang (Yankuang ceshi, 2015)
The accurate identification of host mineral and the formation stage of fluid inclusions are critical to temperature measurement, and the combination of inclusion technology and other technologies could be better to figure out the source and properties. Vug fillings in Middle Permian Qixia Formation of western Sichuan Basin are characterized by the intimate intergrowth of saddle dolomite and calcite. In this paper, Alizarin Red S is successfully used to distinguish the host minerals of fluid inclusions on the basis of the recognition of the sequence of diagenetic authigenic minerals. The results show that the Alizarin red staining techniques used in measuring fluid inclusion temperature of carbonates is feasible due to the difference of homogenization temperature of fluid inclusions before and after Alizarin Red staining is within 1℃. Solution proportion (especially the concentration of hydrochloric acid), dyeing time and the clearing way of staining solution are key parameters to the application of Alizarin red staining technique on the temperature measurement of fluid inclusion. Fluid-inclusion homogenization temperature of saddle dolomite mainly range from 110℃ to 190℃, up close to 270℃, and that of calcite is mainly between 70℃ and 130℃. Formation temperature difference of about 40-60℃ between saddle dolomite and calcite may be related to the Emeishan basalt eruptions in the late Permian. Fluids with high temperature related to the Emeishan basalt eruptions overcome the dolomite precipitation kinetics barrier and cause saddle dolomite precipitated. Saddle dolomite was dissolved and calcite precipitated in the dissolution space of dolomite and inter-granular pores due to the decrease of paleo-temperature after the thermal event.